EXPRESSION OF UNITS VERBALIZING THE CONCEPT OF “FEAR” IN ENGLISH AND UZBEKISTAN THROUGH COGNITIVE SLOTS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article is devoted to the comparative analysis of lexical, phraseological and paremiological units verbalizing the concept of “fear” in English and Uzbek. The article studies the similarities and differences in the classification of cognitive slots of units in both languages.